Features of Рertussis in the Кursk region according to the infectious diseases hospital - E. N. Khokhlova; N. A. Drachevа; T. V. Grishakovа (LLC "Diagnostics and Vaccines", 2020)
Despite the high level of vaccination coverage, whooping cough remains a serious health problem worldwide. The aim of the study was to study the features of the course of pertussis in the Kursk region for the period from January 2016 to October 2019. Materials and methods.83 patients aged from 1 month to 28 years with a confirmed diagnosis of pertussis using PCR or ELISA were monitored.Results: Most cases were reported in the summer-autumn period. Among those with whooping cough, children of the first year of life who did not receive or have not completed vaccination against whooping cough due to age, as well as children older than 1 year who were not vaccinated due to their parents ' refusal to vaccinate prevailed. The diagnosis of whooping cough at the prehospital stage is diagnosed only in 1/3 of cases. Among the clinical forms, combined with the nature of hematological changes, the typical course of pertussis prevailed, which was more severe significantly more often in the group of unvaccinated children of the first year of life.Conclusion. For diagnostics, it is advisable to use PCR as a high-precision and more informative method in comparison with bacteriological research. Currently, there is still a need to develop current vaccination programs and popularize vaccination against pertussis among various population groups, which can serve as a factor in reducing the incidence in the Kursk region.